Hormonal status, age and clinical symptoms related to ovarian volume and stroma among women in perimenopausal age - Jędrzejczyk, Sławomir; Izdebski, Bartosz; Dębowski, Marcin; Jędrzejczyk, Małgorzata; Juchnowicz-Bierbasz, Romuald; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2006)
Aim of study: The aim of this material was comparison of sonographical images of ovaries in women in perimenopausal age to their hormonal status and analysis of the correlation between the age of patients, hormonal status and ovarian volume. Materials and methods: 50 patients aged between 45 and 55 years qualified from 351 who performed hormone measurements less than 5 days before or after ultrasound examination were analyzed. The severity of menopausal symptoms was assessed with the Kupperman index. The ultrasound examinations were performed by one physician and were described according to one pattern. Estimation of uterine corpus, endometrial thickness and structure and ovarian volume and structure of the ovarian stroma were done. Results: There was a significant decrease in mean ovarian volume from 6 cm 3 among premenopausal women to 4.25 cm 3 among perimenopausal women and to 3.5 cm 3 among postmenopausal women. The increase of the FSH level in serum correlates with an increase of the rate of amenorrheal women and women with medium or high severity of menopausal symptoms. Conclusions: A considerable correlation between hormonal status and ovarian volume and their inner structure was observed. In perimenopausal age there is substantial discrepancy between women’s age, presence of menopausal symptoms and the FSH level and ovarian volume. Diminution of ovarian volume in perimenopausal age correlates mostly with the FSH level less with the patient’s age and severity of menopausal symptoms.